Effectiveness of slow dancing movement (hug with husband) on labour pain in active phase I - Ismah Diana; Nor Asiyah; Nasriyah Nasriyah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Labour pain during the first stage is one of the main complaints experienced by women in labour, especially in the active phase when there is an increase in the intensity and frequency of contractions. Various nonpharmacological methods have been recommended for pain management, one of which is the slow dancing technique (hug with husband). Purpose: This study aims to determine the effectiveness of slow dancing movement (hug with husband) on reducing labour pain in active phase I. Method: The research design used a quasi-experiment with a one-group pretest-posttest design. The sample in this study were 45 mothers in labour during the active phase I who met the inclusion criteria. The sampling technique used purposive sampling. Pain measurement was carried out using the Numeric Rating Scale (NRS) scale before and after the slow dancing intervention for 20 minutes with husband assistance. Data were analysed using paired t-test statistical test Results: The difference in the level of labour pain in the first stage before and after the slow dancing movement intervention (hug with husband) in the results of bivariate analysis (Paired t-test) showed that there was a significant difference between the level of pain before and after the intervention (p < 0.05). Conclusion: Slow dancing movement (hug with husband) proved to be effective in reducing labour pain in the first stage. Suggestion: Midwives are expected to integrate slow dancing techniques as part of non-pharmacological pain management in childbirth care and provide education to couples since the antenatal period regarding the importance of husband support during childbirth.